Option A
-x + 6y = 42 is the standard form
Solution:
Given that we have to write [tex]y = \frac{1}{6}x+7[/tex] in standard form
The standard form of an equation is Ax + By = C
In this kind of equation, x and y are variables and A, B, and C are integers
Given equation is:
[tex]y = \frac{1}{6}x+7[/tex]
Let us convert the above equation into standard form
[tex]y = \frac{x}{6} + 7[/tex]
[tex]y = \frac{x}{6} + \frac{7}{1}[/tex]
Make the denominator same in R.H.S
[tex]y = \frac{x}{6} + \frac{7 \times 6}{1 \times 7}[/tex]
Solve the above equation
[tex]y = \frac{x}{6} + \frac{42}{6}[/tex]
[tex]y = \frac{x+42}{6}[/tex]
Move 6 from R.H.S to L.H.S
[tex]6y = x + 42[/tex]
Bring all the terms to one side, leaving only constant on R.H.S
[tex]-x + 6y = 42[/tex]
The above equation is of form Ax + By = C
Thus option A is correct